Concentrations, Sources and Distribution of Polycyclic Aromatic Hydrocarbon (PAHs) Compounds in Basrah soils, Iraq (Baghdad Science Journal, 2023)
Anthropogenic activities cause soil pollution with different serious pollutants, such as polycyclic aromatic hydrocarbon (PAHs) compounds. This study assessed the contamination of PAHs in soil samples collected from 30 sites divided into eight groups (residential areas, oil areas, agricultural areas, roads, petrol stations, power plants, public parks and electrical generators) in Basrah city-Iraq during 2019-2020. The soil characteristics including (moisture, pH, EC and TOC) were measured. Results showed the following ranges (soil moisture (0.03-0.18%),pH (6.90-8.16), EC (2.48-104.80) mS/cm and TOC (9.90-20.50%)). Gas Chromatography (GC) was used to measure PAHs in extracted soil samples. The total PAH range (499.96 - 5864.86) ng/g dry weight (DW). The most dominant percentage of PAHs in (residential areas, oil areas, agricultural areas, roads, petrol stations, power plants, public parks and electrical generators) in dry season were (BghiP 36% , Chy 29% ,BkF 26% , BaP 18% ,BghiP 27% , InP 40% , BbF 19% and BbF 12%) respectively, while in wet season the most dominant PAHs were (Pyr 22% , BbF 16%, BkF 32% , BbF 36% , BkF 38% , Pyr 26% , BbF 43% and Pyr 35%) respectively.  According to some calculated ratios, the sources of PAHs in Basrah soil were mixed between petrogenic and pyrogenic origins. The soil is classified from weakly to heavily contaminated with PAHs.